2019
DOI: 10.1186/s13756-019-0627-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of NEMO-binding domain peptide used to treat experimental osteomyelitis caused by methicillin-resistant Staphylococcus aureus: an in-vivo study

Abstract: PurposeTreatment of chronic osteomyelitis (bone infection) remains a clinical challenge. Our previous study had demonstrated that NEMO-binding domain (NBD) peptide effectively ameliorates the inhibition of osteoblast differentiation by TNF-α in vitro. In this work, NBD peptide was evaluated in vivo for treating chronic osteomyelitis induced by methicillin-resistant Staphylococcus aureus (MRSA) in a rabbit model.MethodsTibial osteomyelitis was induced in 50 New Zealand white rabbits by tibial canal inoculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In our present study, type 1 was the main genotype and the total MR-MP rate was high up to 97.6% (40/41). In addition, the MR-MP rate of genotype 1 and genotype 2 was 100% (37/37) and 75% (3/4) respectively, which was consistent with our previous report [22]. Macrolides are still used as first-line agents at high frequencies in countries with a high burden of MR-MP strains, such as China and Japan, mainly because of their low minimum inhibitory concentrations against the bacteria, anti-inflammatory effect and low toxicity in young children.…”
Section: Discussionsupporting
confidence: 92%
“…In our present study, type 1 was the main genotype and the total MR-MP rate was high up to 97.6% (40/41). In addition, the MR-MP rate of genotype 1 and genotype 2 was 100% (37/37) and 75% (3/4) respectively, which was consistent with our previous report [22]. Macrolides are still used as first-line agents at high frequencies in countries with a high burden of MR-MP strains, such as China and Japan, mainly because of their low minimum inhibitory concentrations against the bacteria, anti-inflammatory effect and low toxicity in young children.…”
Section: Discussionsupporting
confidence: 92%
“…As we already explain in the introduction, there are numerous studies that aim to prevent the colonization of SA in bone from the outset [28][29][30][31][32]. Despite this large spectrum of studies, almost all were only conducted with Methicillin-sensible SA (MSSA) in small animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive chronic osteomyelitis was achieved within 3 weeks of S. aureus infection based on the well-established animal models. 27 , 35 S. aureus is the major pathogen among staphylococci, the most common cause of bone infection, and also activates the NFκB pathway. 32 , 33 Our in vivo study of S. aureus infection showed that NBD peptides exhibited infection-prevention efficacy, with lower infection rate and bacterial quantity, as well as radiological and histological scores for osteomyelitis, comparable to cefazolin, providing an opportunity to selectively abrogate the S. aureus –induced activation of NFκB.…”
Section: Discussionmentioning
confidence: 99%